Literasi Kebudayaan Dan Kewarganegaraan Di SD Islam Terpadu Insan Utama - Zikri Darmawan; Kania Wisna Sashikirana; Naomi Kristina Pangaribuan; Ari Hasriansyah; Febrina Dafit (KOLONI, 2023)
This journal comprehensively discusses the implementation of cultural and civic literacy programs at the Insan Utama Integrated Islamic Elementary School. This report covers various types of literacy that are applied, such as literacy, science literacy, numeracy, cultural and civic literacy, and digital literacy. This journal also documents activities related to Islamic religion carried out in schools. With a habituation, development and learning approach, the Insan Utama Integrated Islamic Elementary School aims to increase students' understanding and participation in culture and citizenship.  Keywords: literacy, culture, citizenship, elementary school